La cognición perceptual. Creencia y razones epistémicas según Leibniz - Vargas, Evelyn (2014)
In this paper I analize Leibniz’s view on sense perception (sensus) in his middle years as an epistemological doctrine in which he combines the demands of external constraint (receptivity) and epistemic justification (normativity). The view is then related to his strategies to refute skeptic arguments concerning the justification of perceptual judgments.